DO ESG-RELATED GOVERNANCE DISCLOSURES IMPROVE FIRM’S FINANCIAL PERFORMANCE IN INDONESIA? - Rahmithasari, Wyandhika Muharani; Qadri, Resi Ariyasa (Center for Economic Studies Universitas Katolik Parahyangan, 2024)
This study endeavors to scrutinize the causality between the transparency of information within the governance pillar of sustainability performance by corporations and their financial outcomes, measured using Tobin's Q. Adopting a quantitative methodology, the research utilizes an inferential statistical testing model to analyze 275 samples derived from non-banking entities listed on the Indonesia Stock Exchange over the period from January 1, 2017, to 2021. The findings elucidate that management dedication and sustainability strategies exert a considerable adverse effect on the financial performance of companies. Conversely, the efficacy of shareholder structures appears to exert no substantial influence on financial outcomes. These results imply the critical need for corporations to meticulously consider governance aspects when devising their strategic plans. An efficacious strategy is pivotal for fostering exemplary governance practices, thereby enabling the organization to judiciously orchestrate sustainability initiatives in alignment with stakeholder perceptions